2008
DOI: 10.1007/s00405-008-0762-1
|View full text |Cite
|
Sign up to set email alerts
|

VCAM-1 and eosinophilia in diffuse sino-nasal polyps

Abstract: The objective of our study was to investigate: the expression of vascular cell adhesion molecule-1 (VCAM-1) in diffuse sino-nasal polyps; the relation between VCAM-1 and selective eosinophilia in diffuse sino-nasal polyps; the effect of eosinophilia and VCAM-1 expression on recurrence of diffuse sino-nasal polyps following treatment. Fifty patients with diffuse sino-nasal polyps were included in the study. Biopsies were taken from the polyps and the inferior turbinate mucosa of each patient and were studied by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…In addition, levels of circulating vascular cell adhesion molecule-1 and its expression in patients with sleep apnea were significantly altered compared with control subjects [29]. In previous studies, the expression of vascular cell adhesion molecule-1 was found to be significantly higher in patients with recurrent nasal polyps [30]. These findings might indicate a "vicious circle".…”
Section: Discussionmentioning
confidence: 91%
“…In addition, levels of circulating vascular cell adhesion molecule-1 and its expression in patients with sleep apnea were significantly altered compared with control subjects [29]. In previous studies, the expression of vascular cell adhesion molecule-1 was found to be significantly higher in patients with recurrent nasal polyps [30]. These findings might indicate a "vicious circle".…”
Section: Discussionmentioning
confidence: 91%
“…Eweiss et al 33 2009 50 Tissue eosinophil (/HPF) Tissue eosinophil level was not different between CRSwNP patients who developed recurrent polyps after ESS and those who did not (p = 1). Non-eosinophil-dominated CRSwNP with positive skin test had the least therapeutic response to 6 weeks of budesonide nasal spray than non-eosinophil-dominated CRS with polyps with negative skin test and those with eosinophil-dominated CRS (p < 0.05).…”
Section: Discussionmentioning
confidence: 92%
“…Increased expression of VCAM-1 is found in NPs, and its levels correlate with eosinophil numbers [1••]. Higher VCAM-1 levels have been found in NPs of patients with recurrent CRSwNP compared with nonrecurrent CRSwNP patients [72].…”
Section: Proinflammatory Mediatorsmentioning
confidence: 99%